AB0763 Bioelectrical impedance analysisfor the assessment of body composition in patients with systemic sclerosis. (12th June 2018) - Cuomo, G.; Guarino, G.; Danzo, F.; Romano, C.; Masini, F.; Ferrara, R.; Gentile, S.; Adinolfi, L.E.
Abstract : Objectives: The aim of the present study was to evaluate the body composition by bioelectrical impedance analysis (BIA) and to assess the nutritional status by BMI and possible correlations with epidemiological and clinical characteristics in patients with SSc Methods: Malnutrition was defined as BMI <18.5 kg/m 2 or unintentional weight loss >10% in combination with a fat-free mass index (FFMI) <15 kg/m 2 for women or <17 kg/m 2 for men or BMI <20.0 kg/m 2 (age <70 years) or <22 kg/m 2 (age >70 years). Body composition was assessed in 40 patients (female) (age mean ±sd: 45.2±12.2) and 20 healthy controls (age mean ±sd 41.5±5.3) with BIA (Akern, Italy) and BMI. The manufacturer's equation and the Geneva equation were used to estimate fat mass (FFM). In addition, correlations with disease activity, gastrointestinal severity, disease subset, autoantibody profile, skin score were evaluated. Results: Malnutrition was found in 10% of patients vs 8% of healty controls; and low FFMI in 30% of patients vs 10 5 of HC. Bioimpedentiometry showed a Fat Free Mass (FFM) (metabolically active component of fat free mass) reduced in patients compared to controls (46.8±7.6 vs 53.6±6.3 respectively; p=0.01). Furthermore, with the same instrument a lower basal metabolic rate was found in patients compared to controls: 1462±145 vs 1720±169 calories (p=0.001). The correlations between FFM and basal metabolism with the clinical features of the patients were not statistically significant Conclusions: This study confrim the study of Spanjer MJ et al 1 and shows a relatively low prevalence of malnutrition in comparison with other studies, but a high prevalence of low FFMI, underlining the necessity of measuring body composition in SSc patients with a standardised and validated method. Furthermore, Caporali et al, 2 have shown an alteration of the nutritional status of patients of SSc probably related to a gastro-intestinal commitment. In our patients despite the presence of an apparent good nutritional status the use of bioimpedanceometry revealed a different body composition, a lower share of muscle mass, in patients compared to controls, related, in part, to musculoskeletal involvement by systemic sclerosis (increase in muscle catabolism and/or poor nutrient supply due to malabsorption phenomena). The early detection of such alterations could be useful to insert subjects at risk in physical rehabilitation programs. References: [1] Spanjer MJet al, Rheumatology2017 [2] Caporaliet al; Clin Nutr2012 Disclosure of Interest: None declared